Kendali Genetik Toleransi Kekeringan pada Padi Sawah (Oryza sativa L.) - Suwarno, Punjung Medaraji; Wirnas, Desta; Junaedi, dan Ahmad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTDrought has become a main barrier of rainfed rice in dry climate and short wet season areas. Growing drought-tolerance varieties is a practical approach to minimize yield lost of rice by the drought stress condition. The aims of this research were to examine the inheritance of drought tolerance character, to identify selection traits, and to estimate genetic gain for drought tolerant on lowland rice. Four rice varieties, i.e., Jatiluhur, Mentik Wangi, IR64, Way Apo Buru, were fully diallel crossed. The parent varieties and the F1’s were grown at Sawah Baru, Dramaga experimental field in two irrigation treatments, optimum and sub optimum where irrigation was applied until three weeks after transplanting. A randomized complete block design with three replications for each irrigation treatment was applied to the experiment. The results showed that there is a significant maternal effect on tiller number. The values of additive variance were higher than the dominance for all other characters except tiller number and grain weight per plant. The highest value for narrow sense heritability was achieved by panicle length.Keywords: diallel, drought, genetic, rice